The need for legal regulation of cryptocurrencies and it’s impact on the economy - Sutyamov, Viktor; Čermáková, Klára; Sáenz de Viteri Vázquez, Andrea; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
Since the advent of blockchain technology and the publication of the new Bitcoin cryptocurrency, many questions about the new field have arisen. In the case of this paper, research into the cryptocurrency field will look at the regulatory side that states are imposing to both protect the consumer and create a transparent taxation system. This study will prove the connection of the cryptocurrency market with the global economy and show what influence the changes in monetary policy can have on it. It will use the OLS model as a statistical approach for analyzing the relationship between one or more independent variables and a dependent variable. It will look at the amount of taxes that can be collected from the European cryptocurrency sector and the fact how this sector benefits national economies. This research can provide implications in regulations and how significantly they can contribute to the country's tax revenue and show the need to regulate the cryptocurrency market
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses